2020
DOI: 10.1111/pce.13970
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration increases under high‐temperature stress: Potential mechanisms, trade‐offs and prospects for crop resilience in a warming world

Abstract: The frequency and intensity of high‐temperature stress events are expected to increase as climate change intensifies. Concomitantly, an increase in evaporative demand, driven in part by global warming, is also taking place worldwide. Despite this, studies examining high‐temperature stress impacts on plant productivity seldom consider this interaction to identify traits enhancing yield resilience towards climate change. Further, new evidence documents substantial increases in plant transpiration rate in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(64 citation statements)
references
References 177 publications
(225 reference statements)
2
61
0
1
Order By: Relevance
“…High-temperature increases transpiration rate and causes water deficit in diverse plants [53]. We found that OsERF115/AP2EREBP110-OE plants showed delayed visual symptoms of water deficit under the combined heat and drought stress conditions compared to WT plants (Figure 4a).…”
Section: Phenotyping Water Use Dynamics Using Droughtspotter Indicates That the Oserf115/ap2erebp110-oe Transgenic Plants Possess Water Smentioning
confidence: 80%
“…High-temperature increases transpiration rate and causes water deficit in diverse plants [53]. We found that OsERF115/AP2EREBP110-OE plants showed delayed visual symptoms of water deficit under the combined heat and drought stress conditions compared to WT plants (Figure 4a).…”
Section: Phenotyping Water Use Dynamics Using Droughtspotter Indicates That the Oserf115/ap2erebp110-oe Transgenic Plants Possess Water Smentioning
confidence: 80%
“…Leaf R is significantly altered by the presence or absence of photosynthesis, particularly in cells that are photosynthetically active (N. G. Smith, Li, & Dukes, 2019). Water availability is especially important when considering extremely hot days and heatwaves, as drought and heat often occur concurrently due to the evaporative effects of heat on soils and the larger VPD between leaves and the surrounding air on hot days (Sadok, Lopez, & Smith, 2020; Teskey et al, 2014). With this in mind, we consider how dark to light transitions, and water limitations, would each impact the high temperature response of leaf R .…”
Section: Environmental Stimuli Interact With the Heat Response Of Respirationmentioning
confidence: 99%
“…Focusing on source‐sink dynamics, they emphasize the relevance of non‐foliar photosynthesis to supply carbon for highly energy intensive reproductive processes (Ferguson et al, 2021). Plant responses under heat are also strongly influenced by relative humidity, which can either enhance (dry air) or lower (moist air) evaporative demand, thus leading to the differential impact of heat stress on plants exposed to similar temperatures (Sadok, Lopez, & Smith, 2021). By examining stomatal‐, cuticular‐ and water viscosity‐based mechanisms, Sadok et al (2021) highlight the need to consider trade‐offs between temperature and evaporative demand while developing new crop varieties for future hotter and drier climates.…”
Section: Carbon Dynamics As a Key Regulator Of Plant Heat Stress Responsesmentioning
confidence: 99%
“…Plant responses under heat are also strongly influenced by relative humidity, which can either enhance (dry air) or lower (moist air) evaporative demand, thus leading to the differential impact of heat stress on plants exposed to similar temperatures(Sadok, Lopez, & Smith, 2021). By examining stomatal-, cuticular-and water viscosity-based mechanisms,Sadok et al (2021) highlight the need to consider trade-offs between temperature and evaporative demand while developing new crop varieties for future hotter and drier climates.The ability to maintain photosynthesis is critical for supplying carbohydrates to fuel metabolism and reproduction during heat stress, and this Special Issue compiles a suite of research papers investigating the response of CO 2 assimilation under warmer conditions Osei- Bonsu, McClain, Walker, Sharkey, and Kramer (2021). highlight the importance of photorespiration and alternative electron sinks in preventing photodamage to Photosystem II (PSII) in high temperature and high light conditions.…”
mentioning
confidence: 99%